A study of teacher wellbeing in post-primary schools in the West of Ireland - Crawford, Teresa (University of Dundee, 2022)
This thesis explores teacher wellbeing in two post-primary schools in the West of Ireland. The research was conducted using a qualitative case study methodology, through semi-structured interviews with twenty-six newly qualified and experienced teachers in two urban schools, one located in a disadvantaged area and the other in a middle-class area.

Research on wellbeing suggests that it is a multi-dimensional concept and difficult to define despite a steep increase in scholarly research across a myriad of disciplines in the last decade. The research pertaining to teacher wellbeing has evolved from predominantly a deficit perspective on stress to an abundance of literature that locates teacher wellbeing at a level of the individual’s capacity to build resources in meeting the challenges inherent in teaching today. However, findings from this study suggest that teaching is a highly complex profession and exploring teacher wellbeing requires a systemic lens as it is experienced within multiple relationships and systems between the teacher, the organisation of the school and external educational trends. These relationships are dynamic, multi-directional often with competing interests yet have a critical role in enhancing teacher wellbeing. I employed Bronfenbrenner’s (1979) ecological systems theory as a framework as it identifies the overlapping layers of context from the micro, meso, exo and macro to capture the complexity of these interacting systems. This was complemented by Jordan’s (2006; 2017) relational cultural theory which offered a further lens to explore the contextual nuances of these relationships, demands and dynamics.

From an ecological, relational-cultural perspective, the study reveals that at the micro level of professional wellbeing, the teacher-student relationship is at the core of being a teacher and is buttressed by three key wellbeing constructs; a strong teacher identity, robust self-efficacy, and the emotional and social capacity to manage and process challenges in teaching. Furthermore, spanning the micro to the meso and exo level of context, mutually empowering relationships with colleagues, parents, leaders, and peers underpinned by a culture of collaboration and a deep connection to place was found to enhance wellbeing while also buffering the impact of macro level challenges. On the whole, teachers in this study embraced the joy of journeying with students and were strengthened by coming through the ‘tough times’ that this could entail. Significantly, it was the raft of other external and cultural demands that took its toll on their wellbeing. This suggests that teacher wellbeing is not solely dependent on the individual’s capacity to access resources to ‘bounce back’ in the face of challenge or adopting a ‘quick fix’ solution. Rather teacher wellbeing resides in the lived reality and in the collective capacity developed in nurturing mutual relationships to navigate the complex ecological terrain unique to each school context and culture. The implications of the study suggest that employing an integrated ecological, relational-cultural lens at whole-school level to commence an open and active discourse on the meaning of wellbeing is critical and that the voice of the teacher must be foregrounded in the process.